Ivan Groznyi - Eisenstein, Sergei (Soviet Union)
Epic story about 16th century Russian tsar Ivan IV, and his role in the unification of the Russian lands. His efforts to build a centralized state meet resistance. The film features the struggle of the tsar against the boyars, with the latter appearing as treacherous and vicious, as well as emphasizing the personal drama of a tyrant.
Keywords: Fiction films